Meningkatkan Kemampuan Mengenal Huruf pada Anak Usia 5-6 Tahun dengan Media Celemek Pintar - Ningrum, Dwi Annisa Sucia; Suryanti, Hera Heru Sri; Ajie, Dina Pertiwi (Universitas Batanghari Jambi, 2024)
The point accomplished by analysts in this inquire about is an exertion to make strides the capacity to recognize letters in children matured 5-6 a long time at the Pembina Tasikmadu Karanganyar State Kindergarten utilizing savvy cook's garments. This inquire about is Classroom Activity Inquire about (PTK). The populace of this inquire about was children matured 5-6 a long time at the Pembina Tasikmadu Karanganyar State Kindergarten, totaling 20 children who were gather B children comprising of 12 young ladies and 8 boys. Information collection strategies utilized in this inquire about were perception, interviews and documentation. The information investigation procedure utilized in this inquire about is subjective information investigation. The comes about of this inquire about appear that utilizing the savvy overskirt media amusement can move forward the capacity to recognize letters in children matured 5-6 a long time at the Pembina Tasikmadu Karanganyar State Kindergarten.